2009
DOI: 10.1590/s1516-35982009001300031
|View full text |Cite
|
Sign up to set email alerts
|

Influência do alimento na produção e qualidade do leite de cabra

Abstract: RESUMO -O leite de cabra é considerado um dos alimentos mais completos por apresentar vários elementos importantes para a nutrição humana, constituído de proteínas de alto valor biológico e ácidos graxos essenciais, além de seu conteúdo mineral e vitamínico. Esta revisão tem como objetivo avaliar as variações referentes à composição química e propriedades físico-químicas do leite, que ocorrem em função de alguns fatores, tais como: climáticos, raça, indivíduo, estágio de lactação e alimentação. O manejo alimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0
24

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(51 citation statements)
references
References 57 publications
0
27
0
24
Order By: Relevance
“…According to these authors, this happened because the increase in the proportion of fiber stimulated the activities of chewing and rumination, stimulating a greater consumption of water. Costa, Queiroga, and Pereira (2009) reported that there was lower consumption of water by lactating goats that received rations with higher levels of fresh cactus -fodder instead of maize corn, without losses to milk production. The estimated water intake according to the NRC (2007) is 2.87 kg day -1 required to meet the requirements of lactating goats, as the average found in this work was 5.766 kg day -1 , resulting in higher values than those estimated (38; 19, 91 and 39%), for the diets SS, BH, SSFP and BHFP respectively.…”
Section: Resultsmentioning
confidence: 99%
“…According to these authors, this happened because the increase in the proportion of fiber stimulated the activities of chewing and rumination, stimulating a greater consumption of water. Costa, Queiroga, and Pereira (2009) reported that there was lower consumption of water by lactating goats that received rations with higher levels of fresh cactus -fodder instead of maize corn, without losses to milk production. The estimated water intake according to the NRC (2007) is 2.87 kg day -1 required to meet the requirements of lactating goats, as the average found in this work was 5.766 kg day -1 , resulting in higher values than those estimated (38; 19, 91 and 39%), for the diets SS, BH, SSFP and BHFP respectively.…”
Section: Resultsmentioning
confidence: 99%
“…According to Costa et al (2009), when the animal advances in its lactation stage, there is a downward trend in the daily milk production and consequently the lactose content decreases, causing an increase in fat and protein levels.…”
Section: Resultsmentioning
confidence: 99%
“…The source of energy is another factor that combined with the forage: concentrate ratio may affect milk composition, both in fat content and in milk fatty acid profile (Costa, Queiroga, & Pereira, 2009).…”
Section: Discussionmentioning
confidence: 99%